ANALISIS PENDAPATAN USAHATANI HIDROPONIK MATUARI DI KELURAHAN PANIKI BAWAH KOTA MANADO - Moh. Rifaldi Ismail; Elsje Pauline Manginsela; Gene H. M. Kapantow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
This study aims to analyze the income of Matuari Hydroponic farming in Paniki Bawah City, Manado. This research was conducted for 3 months, starting from February to April 2019. The data used in this study were primary data and secondary data. Primary data were obtained through interviews with the help of a list of questions prepared in advance. Secondary data were obtained from various sources related to the problems discussed in this study. The results showed that, the income of Matuari Hydroponic farming for celery plants was Rp. 6,216,860.2, with a planting period of 3 months. For caisin plants the farming income was Rp. 640,097.1, with a planting period of 1.5 months. Therefore, the total income of Matuari Hydroponics for 4.5 months planting period was Rp. 6,856,957.3.Keywords: Income, Farming, Matuari, Hydroponic